Comparison of physiological uptake of normal tissues in patients with cancer using 18F-FAPI-04 and 18F-FAPI-42 PET/CT - Mu, Xingyu; Huang, Xiaoxue; Li, Meng; Sun, Wenjie; Fu, Wei (Frontiers in Nuclear Medicine, 2022)
Purpose To calculate the physiological uptake of various tissues in patients with cancer using 18F-AlF-NOTA-FAPI-04 (18F-FAPI-04) and 18F-AlF-NOTA-FAPI-42 (18F-FAPI-42) PET/CT and to compare the variation in standard uptake values between the two scans. Materials and methods This retrospective analysis included 40 patients with cancer who underwent 18F-FAPI; the first 20 patients received 18F-FAPI-04 PET/CT and the remaining 20 patients received 18F-FAPI-42 PET/CT. A total of 49 normal tissues, including the brain (cerebrum/cerebellum), parotid and submandibular glands, palatine tonsils, and thyroid, were identified on CT images. For these normal tissues, maximum standardized uptake value (SUVmax) and mean standardized uptake value (SUVmean) were calculated. We also compared the SUVmean of identical tissues to explore the difference in biodistribution between the two radiotracers. Results The accumulation of 18F-FAPI-04 and 18F-FAPI-42 showed an analogous pattern. High uptake of both radiotracers in the gallbladder, uterus, submandibular gland, and renal pelvis was demonstrated (range: SUVmax, 4.01–5.75; SUVmean, 2.92–4.22). Furthermore, the uptake of bony tissues was slightly higher in 18F-FAPI-42 than in 18F-FAPI-04 (range: SUVmean, 0.4 ± 0.22–0.9 ± 0.34 and 0.3 ± 0.24–0.7 ± 0.18, respectively, p < 0.05), while the uptake of some soft tissues was higher in 18F-FAPI-04 than in 18F-FAPI-42 (range: SUVmean, 0.9 ± 0.24–1.5 ± 0.35 and 0.9 ± 0.26–1.2 ± 0.37, respectively, p < 0.05). Conclusions Both radioligands exhibited similar physiological uptake of normal tissues in patients with cancers. In addition, 18F-FAPI-42 demonstrated higher uptake of bone tissues than 18F-FAPI-04 while showing lower uptake of soft tissues than 18F-FAPI-04.